2016
DOI: 10.5539/gjhs.v8n9p83
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Pregnant Women and Their Neonates

Abstract: Background and Objective:Vitamin D deficiency during pregnancy is a worldwide problem. Studies have reported prevalence ranged 18-84% in pregnant women. Receiving adequate calcium and vitamin D during pregnancy period is necessary for calcium homeostasis, fetal growth and bone mineralization. This study was aimed to determine the prevalence of vitamin D deficiency in pregnant women and their neonates in Shahroud city in the northeast Iran.Methods:In this cross-sectional study, 284 pregnant women and their neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
(53 reference statements)
3
26
1
4
Order By: Relevance
“…Por otro lado, se observó una correlación débilmente positiva entre los valores de 25OHD materna y neonatal (r 2 = 0.173; p = 0.017). Esta correlación fue similar a la reportada por Abbasian, et al 13 para los valores de 25OHD de suero materno y sangre de cordón en una población iraní (r 2 = 0.12; p = 0.053). En nuestro país existen reportes en relación con los valores sanguíneos de vitamina D en diferentes grupos de edad.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por otro lado, se observó una correlación débilmente positiva entre los valores de 25OHD materna y neonatal (r 2 = 0.173; p = 0.017). Esta correlación fue similar a la reportada por Abbasian, et al 13 para los valores de 25OHD de suero materno y sangre de cordón en una población iraní (r 2 = 0.12; p = 0.053). En nuestro país existen reportes en relación con los valores sanguíneos de vitamina D en diferentes grupos de edad.…”
Section: Discussionunclassified
“…En la presente investigación no se encontraron diferencias entre los valores sanguíneos de las madres adolescentes y de las madres adultas. Lo anterior difiere de lo reportado en la literatura en otros grupos poblacionales, en donde las madres adolescentes tienen una mayor pérdida de masa ósea desde el 26 (13) 49 (26) 95 (50) 21 (11) 9 (13) 18 (26) 35 (51) 7 (10) 17 (14) 31 (25) comienzo del embarazo hasta la sexta semana posparto, indicando que la prevalencia de deficiencia de vitamina D en ellas es mayor 13,[23][24][25] . En nuestro estudio se documentó que la tercera parte de las madres presentaron sobrepeso u obesidad al inicio del embarazo, lo cual se incrementó significativamente al final del mismo.…”
Section: Discussionunclassified
“…In our study the serum vitamin D levels in both the groups had no impact on the neonatal birth weight. Similarly in a study published by Maryam et al 20 and Maghbooli et al 21 suggested that there was no significant association of birth weight with serum vitamin D levels. Heather H. Burris et al 22 did not found any association with serum vitamin D levels and hypertensive disorders in pregnancy, in the present study also there was no significant difference between two groups with respect to pregnancy induced Hypertension.…”
Section: Discussion:-mentioning
confidence: 89%
“…High prevalence of VDD in pregnant women reported from Iran (~60-80%; Abbasian et al, 2016;Pirdehghan, Vakili, Dehghan, & Zare, 2016), and even in sunny regions (Cashman et al, 2016;Kelishadi et al, 2013;Olmos-Ortiz, Avila, Durand-Carbajal, & Diaz, 2015;Schneuer et al, 2014) was alarming for the policy makers in the Iran Ministry of Health. As a result, supplementation with 1,000 IU/d of vitamin D3 from the second trimester of pregnancy was recommended to all hospitals and maternal care centres in Iran.…”
Section: Introductionmentioning
confidence: 99%